RHIZOME ROOT STRUCTURE AND BIOMASS CONTENT CAJUPUT PLANT (Melaleuca Cajuput) IN NAMLEA VILLAGE, BURU REGENCY - Hatulesila, Jan Willem; Mardiatmoko, Gun; Tan, Lieke (Forestry Study Program University Of Mataram, 2025)
The pitih wood plant (Melaleuca leucadendra) is a type of plant that belongs to the guava tribe (Myrtaceae) which can produce one of the essential oil products in Indonesia. Eucalyptus plants can be cultivated by generative (seed) and vegetative propagation methods (shoot cuttings with rejuvination techniques, branch cuttings, shoot cuttings, root cuttings, grafts). However, related to the root structure of the rhizome and the value of the biomass content of this plant, it has not been widely published. This is the impetus to conduct research related to the root structure of the rhizome and the biomass content and stored carbon content of the eucalyptus plant section by direct measurement methods in the field and analysis in the laboratory. From the plot of eucalyptus plants, it can be seen that the selected sample has sturdy rhizome roots with similar plant height characteristics, both for the growth rate of the mother plant and the saplings of the mother plant which generally have an even height and are not too.